Road contracting process at the National Highway Institute (2021)
Through the contracting manual of the National Highway Institute, verifying the information through the quality system and the internal documents of the Institute's contracting process, the aim is to identify the inefficiencies that exist in state contracting both at the general and at the general level. within the National Institute of Highways. Using the Manual of Good Practices in Contract Management as a tool. In this way, it is possible to analyze the inefficiencies in the planning, pre-contractual and contractual stages of the contracting that takes place in the National Institute of roads. Identifying essential processes such as the establishment of a certain time in the pre-contractual and contractual stages. Identifying as a critical stage the document of previous studies that determines the risks that may be incurred by the contract winner as well as the entity. To recommend guidelines, the process that is carried out in California through the Code of regulations is analyzed, which has a different approach from that implemented in Colombia in its planning and pre-contractual stage.